The gamification of work: Lessons from crowdsourcing - Morschheuser, Benedikt; Hamari, Juho (Journal of Management Inquiry, 2019)
The nature of work and management are in flux; work is increasingly distributed, sporadic, community-driven, and motivated by constant self-development. Developments such as sharing economies, crowdfunding, and crowdsourcing have emerged as new forms of organizing work and economic coordination. At the same time, increased gaming and gamification of our lives have arrived to address this newly found yearning for intrinsically motivated work. Thus, work is increasingly consciously and unconsciously gamified. Crowdsourcing is a frontrunner management domain in employing gamification to positively affect motivation and performance of workers. However, to be able to harness the full potential of gamification, a union of knowledge of interwoven areas of game design, motivational psychology and management is needed. Therefore, in this article, based on the accumulated body of research on gamification in crowdsourcing, we discuss the emerging opportunities and challenges of using gamification in management.
CRIS-Team Scopus Importer:2021-02-01
Keywords: Gamification; Crowdsourcing; Human Computation; Motivation; Participation; Human resource; Work